SEJARAH DINAR EMAS DAN KRONOLOGI PERTUKARAN MATA WANG DUNIA - Yaacob, Salmy Edawati (Journal of Al-Tamaddun, 2009)
Currency values measured in gold and silver stabilized the world monetary system in mankind’s history until it was abandoned by paper money. The use of gold and silver (dinar and dirham) was practiced by Prophet Muhammad s.a.w and continued by his companions and the next dynasties of Islam. Gold as the substance of dinar and silver as the substance of dirham were recommended to be used as the only medium of exchange at the time. The Islamic currency (dinar and dirham) itself was one of the great currencies and powers in the world. Therefore, this article exposes the historical of gold dinar and also reveals the chronology of world currency development from using gold as money until it was superceded by paper money.